2017
DOI: 10.1111/jsr.12589
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of insomnia symptoms and nightmares among individuals with post‐traumatic stress disorder: an ecological momentary assessment study

Abstract: Despite the high levels of comorbidity between post-traumatic stress disorder (PTSD) and sleep disturbance, little research has examined the predictors of insomnia and nightmares in this population. The current study tested both PTSD-specific (i.e. PTSD symptoms, comorbid anxiety and depression, nightmares and fear of sleep) and insomnia-specific (i.e. dysfunctional beliefs about sleep, insomnia-related safety behaviours and daily stressors) predictors of sleep quality, efficiency and nightmares in a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 36 publications
(57 reference statements)
3
37
2
Order By: Relevance
“…Another noradrenergic receptor antagonist that has been used primarily to combat disordered sleep in individuals with PTSD is the α1-AR antagonist prazosin. Prazosin has shown promise in ameliorating nightmares and sleep disturbances associated with PTSD (Raskind et al, 2003 ; Taylor et al, 2008 ; Koola et al, 2014 ; Writer et al, 2014 ; de Dassel et al, 2017 ; Keeshin et al, 2017 ; Miller et al, 2017 ; Short et al, 2018 ). However, a recent clinical trial demonstrated that prazosin did not ameliorate sleep-related disturbances in military veterans with PTSD (Raskind et al, 2018 ).…”
Section: Ne and Ptsdmentioning
confidence: 99%
“…Another noradrenergic receptor antagonist that has been used primarily to combat disordered sleep in individuals with PTSD is the α1-AR antagonist prazosin. Prazosin has shown promise in ameliorating nightmares and sleep disturbances associated with PTSD (Raskind et al, 2003 ; Taylor et al, 2008 ; Koola et al, 2014 ; Writer et al, 2014 ; de Dassel et al, 2017 ; Keeshin et al, 2017 ; Miller et al, 2017 ; Short et al, 2018 ). However, a recent clinical trial demonstrated that prazosin did not ameliorate sleep-related disturbances in military veterans with PTSD (Raskind et al, 2018 ).…”
Section: Ne and Ptsdmentioning
confidence: 99%
“…Ecological momentary assessment (EMA), a method of repeated experience sampling of subjects in their natural environment, is well-suited to assessing change in symptoms over time [30,31]. Recent studies have used EMAs to examine PTSS from day to day [32][33][34][35], sleep diaries to examine sleep disturbance from night to night [8,36], and EMAs and sleep diaries combined to examine the temporal relationship between sleep disturbance and PTSS [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Short et al [38] examined the relationship between the previous night's sleep disturbance (i.e., sleep duration, efficiency, quality, and nightmares) and the next day's PTSS in a community and undergraduate sample with PTSD (N = 30; 61.3% female) and found, after accounting for the prior evening's PTSS, reduced sleep efficiency and poor sleep quality (but not sleep duration or nightmares) predicted increased PTSS and negative affect the next day. In another study that used the same sample but changed the direction of the analyses, Short et al [39] examined the relationship between PTSS and subsequent sleep disturbance (i.e., sleep efficiency, quality, and nightmares) and found elevated PTSS predicted increased nightmares (but not sleep efficiency or quality) the following night. Dietch et al [37] examined the bidirectional relationship between sleep disturbance (i.e., sleep duration and quality) and PTSS in a sample of World Trade Center responders oversampled for PTSD (N = 202; 82.7% male; 19.3% with PTSD) and found reduced sleep duration (but not sleep quality) predicted increased PTSS the following day and increased PTSS predicted reduced sleep duration and quality the following night.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some findings that point to a role of fear-related cognitions. For example, studies have found that fear of sleep (Kanady et al, 2018;Pruiksma et al, 2014;Short, Allan, Stentz, Portero, & Schmidt, 2018) linked to nightmares (Davis et al, 2011;Krakow, Tandberg, Scriggins, & Barey, 1995), and fear of loss of vigilance (Pietrzak, Morgan, & Southwick, 2010) are associated with worse sleep and more severe PTSD symptoms in trauma survivors. These findings are consistent with relationships proposed in the maintenance of PTSD symptoms by Ehlers and Clark's (2000) cognitive model of PTSD.…”
Section: Introductionmentioning
confidence: 99%